Hydroenergetics Fundamentals, Types of Hydroelectric Power Stations, Their Advantages, and Disadvantages (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article explores the foundational concepts of hydroenergetics, focusing on the various types of hydroelectric power stations and their operational principles. It provides an in-depth analysis of the key advantages and disadvantages of different types of hydroelectric stations, emphasizing their role in sustainable energy production. The article discusses the potential of hydroelectric power as a renewable energy source and its impact on the environment and economy. Additionally, it examines the technical and operational challenges associated with hydroelectric stations, as well as the factors influencing their efficiency and long-term sustainability.